Barriers to E-Commerce adoption; Among Small and Medium Sized Enterprises (SMEs) ; within the central region of Malaysia / Anis Suraya Abdullah - Abdullah, Anis Suraya (Faculty of Business and Management, 2018)
The purpose of this study is to investigate the barriers to e-commerce adoption among Small and medium sized Enterprise (SMEs) within the central region of Malaysia. A theoretical framework comprises of four (5) factors (external environment, internal environment, perceptions, and attitudes). A multivariate likert-scale questionnaire (scale from 1 to 5) were developed. A sample of 100 questionnaires were distributed to SME in central region of Malaysia but only 73 were returned. Data collected were analysed using SPSS V23. Multiple regression generated to test hypothesis and to establish the effect of external environment, internal environment, perceptions, and attitudes on e-commerce adoption. Regression analysis was conducted to establish. The result of the research shows that only external environment has significant relationship towards e-commerce adoption. Findings also shows that negative external environment will lead to non-adoption of e-commerce in central region of Malaysia. Therefore, the government should take this issue into consideration when they planned for initiative bolstering SMEs’ involvement in digital economy.